2013
DOI: 10.1038/jid.2012.406
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Extracellular Superoxide Dismutase Induces Severe IL-23-Mediated Skin Inflammation in Mice

Abstract: Psoriasis is a common chronic and complex autoimmune inflammatory skin disorder. The histological characteristics of psoriasis are epidermal hyperplasia, mononuclear leukocyte infiltration into the dermis, and increased angiogenesis. However, the mechanisms involved in the pathogenesis of psoriasis remain unclear. Extracellular superoxide dismutase (EC-SOD) has antichemotactic activities. Because immune cell infiltration is seen in psoriatic lesions and psoriasis patients express low levels of EC-SOD, we hypot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 41 publications
2
41
0
Order By: Relevance
“…Topical application of TPA induces IL1a-mediated acute and chronic inflammation and hyperplasia in mouse skin (Lee et al, 1994). In addition, intradermal IL-23 injection into the ears of mice induces chronic inflammation (Zheng et al, 2007;Rizzo et al, 2011;Maddur et al, 2012;Kim et al, 2013;Lee et al, 2013). These stimuli induce inflammatory responses in the skin that increase dermal edematous swelling, erythema, leukocyte infiltration, epidermal hyperplasia, and proliferation of epidermal keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Topical application of TPA induces IL1a-mediated acute and chronic inflammation and hyperplasia in mouse skin (Lee et al, 1994). In addition, intradermal IL-23 injection into the ears of mice induces chronic inflammation (Zheng et al, 2007;Rizzo et al, 2011;Maddur et al, 2012;Kim et al, 2013;Lee et al, 2013). These stimuli induce inflammatory responses in the skin that increase dermal edematous swelling, erythema, leukocyte infiltration, epidermal hyperplasia, and proliferation of epidermal keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the TPA-induced acute inflammatory model, we assessed a chronic inflammatory model by intradermal injection of IL-23 into the ears of mice (Zheng et al, 2007;Rizzo et al, 2011;Maddur et al, 2012;Kim et al, 2013;Lee et al, 2013). Intradermal IL-23 injection into mouse ear skin induced psoriasiform dermatitis that leads to ear thickness, edematous swelling, vascular permeability, and epidermal cell proliferation.…”
Section: Yg-ii-6 Compounds Suppress Cutaneous Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…EC-SOD knockout mice develop severe IL-23-mediated skin inflammation. The infiltration of immune cells at IL-23 injection sites and the expression of proinflammatory cytokines and chemokines are more elevated in these mice [126]. Interestingly, the IQM-induced mouse model shows an aberrant antioxidant system, with increased levels of myeloperoxidase and oxidative stress but less SOD activity.…”
Section: Cellular Antioxidantsmentioning
confidence: 99%
“…Second, it is possible that ecSOD activity could impact the integrity of the HA itself. It has been shown that ecSOD activity protects tissues during noninfectious inflammation in the lung (20)(21)(22)(31)(32)(33)(34)(35). However, whether ecSOD activity protects the ECM from degradation in the basal state or during infection-induced inflammation has not been thoroughly investigated.…”
Section: Resultsmentioning
confidence: 99%